Blood Flow Restriction Training: A Tool to Enhance Rehabilitation and Build Athlete Resiliency - Mark Murphy, P.T., D.P.T., S.C.S., C.S.C.S. (Arthroscopy, Sports Medicine, and Rehabilitation)
Blood flow restriction training (BFRT) is a tool utilized in rehabilitation and injury prevention to improve muscle strength and size, particularly in load-compromised individuals. BFRT facilitates gains in muscular strength and hypertrophy at lower loads, allowing for accelerated recovery and less disuse atrophy. BFRT must be applied appropriately and with caution, particularly in individuals with cardiovascular concerns. There are applications for BFRT across a wide spectrum of human performance training and in rehabilitation of both lower and upper extremity conditions, providing a high-quality adjunct to improve muscle strength, power, and endurance. Level of Evidence: Level V, expert opinion.